PENGARUH PENGENDALIAN FRAUD KEUANGAN PADA TRANSAKSI LETTER OF CREDIT (L/C) TERHADAP REPUTASI BANK BWS KANTOR PUSAT JAKARTA - Wina Suherlina; Winna Sarikusumaningtyas; Boma Jonaldy Tanjung (STKIP Subang, 2026)
This study aims to quantitatively evaluate the impact of financial fraud management in Letter of Credit (L/C) transactions on the reputation of Bank BWS Head Office Jakarta. L/C transactions remain highly susceptible to fraud risks such as document forgery, data manipulation, and abuse of authority, which can diminish public trust. Employing a quantitative associative design (explanatory research), data were gathered from 50 targeted respondents across international transactions, trade finance, operations, internal audit, and risk management divisions selected via purposive sampling. Primary data were collected using a 5-point Likert scale questionnaire and analyzed using simple linear regression and t-test using SPSS 26. The empirical findings indicate that financial fraud management in L/C transactions has a positive and significant effect on the bank's reputation, as evidenced by calculated t = 17.661 > ttabel = 2.011 with a significance level of p = 0.000 < 0.05. The coefficient of determination (R² = 0.867) demonstrates that fraud control accounts for 86.7% of the variance in bank reputation. Strengthening internal control systems and risk management strategies are thus vital imperatives for safeguarding institutional trust.